An Adaptive Threshold Dynamics Method for Three-Dimensional Wetting on Rough Surfaces (Communications in Computational Physics, 2020)
We propose an adaptive threshold dynamics method for wetting problemsin three space dimensions. The method is based on solving a linear heat equationand a thresholding step in each iteration. The heat equation is discretized by a cell-centered finite volume method on an adaptively refined mesh. An efficient techniquefor volume conservation is developed on the nonuniform meshes based on a quick-sorting operation. By this method, we compute some interesting wetting problems oncomplicated surfaces. Numerical results verify some recent theories for the apparentcontact angle on rough and chemically patterned surfaces.
Keywords: Adaptive; threshold dynamics method; wetting.